2021
DOI: 10.3390/pharmaceutics14010024
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Head Model Choice on the In Vitro Evaluation of Aerosol Drug Delivery

Abstract: There are variations in the values reported for aerosol drug delivery across in vitro experiments throughout the published literature, and often with the same devices or similar experimental setups. Factors contributing to this variability include, but are not limited to device type, equipment settings, drug type and quantification methods. This study assessed the impact of head model choice on aerosol drug delivery using six different adults and three different paediatric head models in combination with a fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Collection of aerosol on a filter distal to the trachea represents the aerosol entering the lungs but does not allow for the small proportion of exhaled aerosol observed in vivo , consequently overestimating lung delivery in vivo , but serving as an accepted method to compare the effects of different conditions. It has been found that representative head model choice can significantly affect aerosol delivery [ 11 ]; thus, future studies are required to investigate how this combinational approach to aerosol therapy would affect aerosol deposition in vivo with, for example, scintigraphy studies. Supplemental oxygen is often used to deliver therapeutics to patients with exacerbations of COPD or asthma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Collection of aerosol on a filter distal to the trachea represents the aerosol entering the lungs but does not allow for the small proportion of exhaled aerosol observed in vivo , consequently overestimating lung delivery in vivo , but serving as an accepted method to compare the effects of different conditions. It has been found that representative head model choice can significantly affect aerosol delivery [ 11 ]; thus, future studies are required to investigate how this combinational approach to aerosol therapy would affect aerosol deposition in vivo with, for example, scintigraphy studies. Supplemental oxygen is often used to deliver therapeutics to patients with exacerbations of COPD or asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental Set Up Both gas and aerosol via HFNO and LFNO were delivered through nasal cannula placed in the nares of an anatomically correct 3D printed adult head model, detailed by Gallagher et al 2021 [11]. Concurrent aerosol was administered via a mouthpiece with a valved aerosol holding chamber (Aerogen Ultra, Aerogen Ltd., Ireland) and VMN.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been accepted that as the supplemental gas flow rate increases, the quantity of aerosol available at the lungs decreases [ 13 , 19 , 21 , 29 ]. The differences in reported values between this study, from 0.38 ± 0.09% to 15.99 ± 0.71% adult and from 0.52 ± 0.26% to 4.07 ± 0.45% paediatric, and others can be attributed to differences in the breathing pattern [ 25 , 30 ], head model [ 35 ], HFNO system [ 16 ] and cannula sizes [ 36 ]. However, the findings presented in this work, for both models irrespective of lung health, follow the same trends as these and numerous other published works.…”
Section: Discussionmentioning
confidence: 81%
“…A previously described airway model of the adult nose–throat region was used as the adult model ( 17 ).…”
Section: Methodsmentioning
confidence: 99%